Learning Styles and Gender Effects on Secondary School Students’ Learning Outcomes in Ijebu-Ode Community, Ogun State, Nigeria - Olubela, Afolabi; Adebanjo, Adedoyin (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
Students’ learning styles can help to enhance effective teaching and learning. Making students aware of their learning styles and showing them their individual strengths and weaknesses can help students to understand why learning is sometimes difficult for them and is for developing their weaknesses. The study adopted a pre-test, post-test, control group switching replication quasi-experimental design. Switching replication quasi-experimental design was used in order to increase the internal validity of the study and to establish the efficacy of the treatment. Two Local Government (Ijebu North & Ijebu Ode) Areas in Ogun State were purposively selected. The main instrument used for the study was Learning Styles Self-Assessment Test (LSSAT). LSSAT was an adaptation of the Learning Style Scale developed by Clark (2011), designed to help identify how students prefer to learn. The result of the main effect of learning style on the students’ achievement scores in the first phase and after the second phase (i.e. after switching replication) show non-significant main effect of learning style on the students’ achievement scores. It was recommended that teachers should evaluate their students’ lesson plans to identify which learning modality - visual, auditory or kinesthetic- is best suited for each particular lesson. Keywords : Learning styles, Learning outcomes, Gender, Teaching-learning, Civics, Biology